1984
DOI: 10.1007/bf00251468
|View full text |Cite
|
Sign up to set email alerts
|

Detection of malignant soft tissue tumors in bone imaging

Abstract: A total of 2530 consecutive bone scans were examined to evaluate the number and the type of soft tissue neoplasms detected with bone-seeking phosphonates. Sixty-eight primary or secondary soft tissue neoplasms of 63 patients accumulated 99mTc -methylene diphosphonate and 2 accumulated 99mTc -diphosphonate, and one metastasis was seen as a nonactive 'cold' focus in the urinary bladder. The localization of tumors was: 19 in the lung, 15 in the liver, 11 in the kidney, 10 in the peritoneal cavity or ascites, 5 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…In our earlier studies it was demonstrated that " m Tc-GP accumulated in pathological but not in normal bone tissue (2,3). Accumulation of " m Tc-labelled phosphate compounds in soft-tissue tumors was also reported by Vorne and Sauk- ko (9). The present study was undertaken in a large group of patients to investigate the potential of " m Tc-GP as a radiopharmaceutical in demonstrating bone pathologies in comparison with 9t)m Tc-MDP and lung cancer in comparison with 67 Ga-citrate.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…In our earlier studies it was demonstrated that " m Tc-GP accumulated in pathological but not in normal bone tissue (2,3). Accumulation of " m Tc-labelled phosphate compounds in soft-tissue tumors was also reported by Vorne and Sauk- ko (9). The present study was undertaken in a large group of patients to investigate the potential of " m Tc-GP as a radiopharmaceutical in demonstrating bone pathologies in comparison with 9t)m Tc-MDP and lung cancer in comparison with 67 Ga-citrate.…”
Section: Introductionsupporting
confidence: 64%
“…Being a glucose analogue its uptake mechanism was thought to be through active transport by metabolically active tumor tissue, like that of 18 F-deoxyglucose (6,10) and N-( 18 F)-fluoroacetyl-D-glucos- amine (5). A similar compound, " m T cglucoheptonate, was also reported to accumulate in lung tumors (9). However, GP contains a phosphate group facilitating " m T c labelling, and consequently its in vivo behavior might be similar to that of the other " m T clabelled phosphate compounds used for bone imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that mesothelioma tumors have been reported to accumulate Tc-99m hydroxymethylene diphosphonate in patients with mesothelioma suggests that these cells may possess a yet to be identified mechanism to accumulate bisphosphonates, which may also explain their in vivo sensitivity to these drugs. Such an extraosseous accumulation of the bone scanning agent has also been described for several other epithelial cancer cells, including small cell lung cancer (19,22,34). Interestingly, it was shown recently that treatment with zoledronate also significantly inhibited the growth of small cell lung cancer cells in the flanks of nude mice (35).…”
Section: Discussionmentioning
confidence: 57%